Axial impact behaviors of stub concrete-filled square steel tubes. Issue 11 (August 2019) - Zhang, YT; Shan, B; Xiao, Y
Existing research on the widely used concrete-filled steel tubes is mainly focused on static or cyclic loading, and the studies on effects of high strain rate are relatively rare. In this article, seven stub concrete-filled steel tubular columns with square section were tested under both static and impact loads, using a large-capacity drop-weight testing machine. The research parameters were variable height of the drop-weight and different load types. The experimental results show that the failure modes of the concrete-filled steel tube columns from the impact tests are similar with those under static load, characterized by the local buckling of the steel tube. The time history curves of impact force and steel strain were investigated. The results indicate that with increasing impact energy, the concrete-filled steel tube stub columns had a stronger impact-resistant behavior. The dynamic analysis software LS-DYNA was employed to simulate the impact behaviors of the concrete-filled steel tube specimens, and the finite element results were reasonable compared with the test results. The parameter analysis on the impact behavior of concrete-filled steel tube columns was performed using the finite element model as well. A simple method was proposed to calculate the impact strength of square concrete-filled steel tube columns and compared favorably with experimental results.